2009
DOI: 10.1103/physrevlett.102.212501
|View full text |Cite
|
Sign up to set email alerts
|

γ-Ray Spectroscopy at the Limits: First Observation of Rotational Bands inLr255

Abstract: The rotational band structure of 255Lr has been investigated using advanced in-beam gamma-ray spectroscopic techniques. To date, 255Lr is the heaviest nucleus to be studied in this manner. One rotational band has been unambiguously observed and strong evidence for a second rotational structure was found. The structures are tentatively assigned to be based on the 1/2-[521] and 7/2-[514] Nilsson states, consistent with assignments from recently obtained alpha decay data. The experimental rotational band dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…[45]. With that, the proton pairing strength is significantly larger than that given by the standard value of V n = V p = −1250 MeV fm 3 used for heavy nuclei in previous publications [39,7,[40][41][42][43] (which all have been carried out using the Lipkin-Nogami (LN) scheme, though). These previous values were obtained by adjusting moments of inertia in rotational bands of heavy nuclei [45].…”
Section: Skyrme Energy Density Functional Sly4mentioning
confidence: 83%
See 1 more Smart Citation
“…[45]. With that, the proton pairing strength is significantly larger than that given by the standard value of V n = V p = −1250 MeV fm 3 used for heavy nuclei in previous publications [39,7,[40][41][42][43] (which all have been carried out using the Lipkin-Nogami (LN) scheme, though). These previous values were obtained by adjusting moments of inertia in rotational bands of heavy nuclei [45].…”
Section: Skyrme Energy Density Functional Sly4mentioning
confidence: 83%
“…For the coupling constants of the so-called time-odd terms that contribute to cranked and blocked states, the same "hybrid" choice was made as in many earlier calculations [7,[31][32][33][38][39][40][41][42][43][44]. They were set to the "native" values dictated by a density-dependent Skyrme two-body force for all terms except for those that multiply terms that couple two derivatives and two Pauli spin matrices.…”
Section: Skyrme Energy Density Functional Sly4mentioning
confidence: 99%
“…While in Refs. [3,26] the 1/2 − [521] level was assigned to the ground state, in Ref. [7] the lowest rotational band was found to be built on the 9/2 + [624] state.…”
Section: B Spectrum Of 255 Lrmentioning
confidence: 99%
“…The spin-orbit interaction strength of 2f 5/2 − 2f 7/2 partner controls whether the proton Z = 114 is a magic number for the "island of stability" for shell stabilized superheavy nuclei. Rotational bands based on π 1 2 − [521] orbital have been observed in odd-proton nuclei 251 Md [13] and 255 Lr [14]. Studies of these rotational bands found a significant signature splitting [15,16].…”
Section: Moments Of Inertiamentioning
confidence: 99%
“…The spin-orbit interaction strength of 2f 5/2 − 2f 7/2 partner governs the size of the Z = 114 spherical shell gap, which is predicted as the possible next magic proton number beyond lead. The properties of single-particle orbitals π 7 2 − [514] and π 1 2 − [521] effect strongly the properties of the neighboring odd-Z nuclei [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%